Analysis of distributions of indoor radon concentrations in the regions of the Russian Federation - D. V. Kononenko (Радиационная гигиена)
During 2001–2017 more than 800 thousand records containing the results of measurements of radon concentration taken in 78 regions of Russia were accumulated in the Federal databank of radiation doses to the population of the Russian Federation. The paper presents the procedure and results of the first data analysis carried out to check the conformity of radon concentrations in the regions of Russia with the lognormal distribution and to calculate the parameters of these distributions. The procedure included verification and validation of data, plotting the frequency distribution histograms and Q-Q plots (normal probability plots) and the use of some methods of elimination of plateaus on the Q-Q plots and the distribution recovery. As a result, in 74 of 78 analyzed regions radon concentrations conform quite well or almost perfect to a lognormal distribution up to a certain level (this level ranged from 55 to 4915 Bq/m3). For all 78 regions geometric means with 95% confidence intervals, geometric standard deviations and arithmetic means were calculated. It should be noted that due to the fact that the Federal databank is a database containing results of measurements taken with different techniques (instant measurements, charcoal canisters, radon monitors and etched track detectors), the lognormal distributions for most regions are in fact contaminated distributions, and currently it is impossible to calculate the parameters of separate distributions that form the mixture. The results show that dose assessment based on arithmetic means could lead to an  overestimation of the doses from radon up to 2.1 times compared to that based on geometric means. The calculated medians can also be used for risk assessment purposes.